Über die Formalisierung und Analyse medizinischer Prozesse im Kontext von Expertenwissen und künstlicher Intelligenz - Philipp, Patrick (Karlsruher Schriften zur Anthropomatik, 2023)
Digitalization has already transformed many areas of the economy and social life. Aspects of healthcare and clinical practice are also undergoing digital transformation. In light of these developments, this dissertation sheds light on the acquisition, representation, and use of process knowledge in the context of hybrid AI methods. The central contribution is the structure-preserving back-and-forth transformation of process trees to process plans.